2017
DOI: 10.12819/2017.14.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Relacionamentos Intergeracionais em Famílias de Crianças com Deficiência

Abstract: Editor Científico: Tonny Kerley de Alencar Rodrigues Artigo recebido em 04/08/2017. Última versão recebida em 18/09/2017. Aprovado em 19/09/2017. Avaliado pelo sistema Triple Review: a) Desk Review pelo Editor-Chefe; e b) Double Blind Review (avaliação cega por dois avaliadores da área).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
2
0
5
Order By: Relevance
“…Some grandparents pointed to the importance of faith and belief. This corresponded with Yamashiro and Matsukura (2014) and Lehmann et al (2011) , who agreed with this idea as an important element of learning and/or a tool for coping with having a grandchild with a disability. Most reported changes in their lives since their grandchildren’s birth, and one can compare this narrative to other studies ( Woodbridge et al, 2011 ; Miller et al, 2012 ; Findler, 2014 ; Kresak et al, 2014 ; Yang et al, 2018 ) that describe how grandparents often delayed their life goals.…”
Section: Discussionmentioning
confidence: 56%
“…Some grandparents pointed to the importance of faith and belief. This corresponded with Yamashiro and Matsukura (2014) and Lehmann et al (2011) , who agreed with this idea as an important element of learning and/or a tool for coping with having a grandchild with a disability. Most reported changes in their lives since their grandchildren’s birth, and one can compare this narrative to other studies ( Woodbridge et al, 2011 ; Miller et al, 2012 ; Findler, 2014 ; Kresak et al, 2014 ; Yang et al, 2018 ) that describe how grandparents often delayed their life goals.…”
Section: Discussionmentioning
confidence: 56%
“…Hornby & Ashworth (1994) detected the emotional support given by grandparents, with parents of children with disabilities reported that half of all grandparents participating in the study always understand any problems related to their child with disabilities and a third of them were always willing to listen to parents discuss problems. Yamashiro & Matsukura (2014) affirmed that the support practices exercised in the family context are part of the grandparents' daily lives and are an important source of support for mothers and grandchildren. They also highlighted the importance of intergenerational relationships, considering the benefits they produce for both generations involved.…”
Section: Resultsmentioning
confidence: 99%
“…Assim, o suporte social pode ser utilizado pelas famílias no sentido de organizar os cuidados (Gallimore, Coots, Weisner, Garnier, & Guthrie, 1996). Foram recuperados estudos brasileiros que investigaram famílias com pessoas com deficiência, identificando que os avós fazem parte da rede de apoio familiar (Grisante & Aiello, 2012;Matsukura & Yamashiro, 2012;Oliveira & Matsukura, 2013;Rooke et al, 2019;Sá & Freitas, 2017;Yamashiro & Matsukura, 2014), sendo que as práticas de apoio exercidas pelos avós estão integradas à rotina destas famílias, constituindo importante fonte de apoio às mães e aos netos, visto que as avós auxiliam no cuidado e nas atividades do cotidiano. Estudos internacionais apresentam resultados semelhantes (Findler, 2000;Yang et al, 2018).…”
Section: Avós Como Rede De Apoio Em Famílias Com Crianças Com Deficiência Intelectualunclassified
“…A busca na literatura na área de avós recuperou investigações com famílias com criança com: perda auditiva (Tutiven, Paucar, Brito, & Blume, 2017), autismo (Engstrand, Pettersson, Allodi, & Hirvikoski, 2019;Hillman, 2007;Sullivan, Winograd, Verkuilen & Fish, 2012), deficiência intelectual (Findler, 2014;Hornby & Ashworth, 1994;Yamashiro & Matsukura, 2014, paralisia cerebral (Sá & Freitas, 2017), incluindo a síndrome de Down (Grisante & Aiello, 2012, Hasting et. al, 2002.…”
Section: Avós Como Rede De Apoio Em Famílias Com Crianças Com Deficiência Intelectualunclassified
See 1 more Smart Citation